Treatment of mechanically failed triple pelvic osteotomies in four dogs - part 2 - Fitch, R. B.; Kerwin, S.; Hosgood, G.; Marquis, R. D.; Pluhar, E.; Kudnig, S. T. (Veterinary and Comparative Orthopaedics and Traumatology, 2002)
Four dogs treated with triple pelvic osteotomies (TPOs) with loss of fixation secondary to screw loosening are reported. Two of the patients were revised with an additional ventral plate with successful outcomes. Revision TPO, with additional ventral plate fixation, was highly effective as a salvage technique for failed TPOs.
Keywords: Hip dysplasia; triple pelvic osteotomy; implant loosening